Isolasi dan Uji Aktivitas Antioksidan Senyawa Metabolit Sekinder dari Fraksi n-Butanol Daun Tin (Ficus carica L.) Varietas Brown Turkey - Haris Nanda Prayoga; noveri rahmawati (Jurnal Penelitian Farmasi Indonesia, 2019)
Tin leaf (Ficus carica L.) is one of the traditional medicines that has potential as an antioxidant. The purpose of this study was to isolate secondary metabolites and to test the antioxidant activity of pure isolates from the n-butanol fraction of tin leaves. Extraction was carried out by the fractionation method using n-hexane, ethyl acetate and n-butanol. Then the n-butanol fraction was separated by column chromatography and antioxidant activity was tested using the DPPH method. Pure isolate compounds labeled HNF-3, in the form of crystals, white with a melting point 189-191 ° C. Based on phytochemical examination data analysis, UV spectroscopy, FT-IR and 1H-NMR it can be concluded that the HNF-3 compound is a flavonoid glycoside group and has a moderate category of antioxidant activity with an IC50 value of 160.613 µg / mL.